PENDAMPINGAN MELALUI PROGRAM KAMPUS MENGAJAR DI UPT SPF SD NEGERI PATTINGALLOANG I MAKASSAR - Shasliani; Syaidah; Nur Ilmi; Eka Putri Atjo, Syamsuryani; Aras, Latri (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2024)
The Teaching Campus Program is part of the Independent Learning Campus (MBKM) policy from the Ministry of Education, Culture, Research and Technology (Kemendikbudristek). This program provides students with the opportunity to learn outside the study program by becoming partners with teachers in developing creative, innovative and fun learning strategies in primary and secondary education units. By implementing this program, students are encouraged to develop 21st century skills and skills (analytical thinking, problem solving, leadership, team management, creativity and innovation, interpersonal communication). The Class 7 Teaching Campus aims to equip students with a variety of expertise and skills by becoming partners with teachers and schools in developing learning models, and can also foster creativity and innovation in learning so that it has an impact on strengthening literacy and numeracy learning, adapting technology, and providing administrative assistance in schools. This activity was carried out by the Class 7 UPT SPF Teaching Campus at Pattingalloang I Makassar State Elementary School, Makassar city. This activity starts on February 19 – June 9 2024. The result of the activity is that the mentoring program has run well because it has met expectations. The conclusion of this activity is that the 7th Class UPT SPF Teaching Campus Program at Pattingalloang I Makassar State Elementary School in South Sulawesi Province has had a positive impact on students of UPT SPF Pattingalloang I Makassar State Elementary School, Makassar City